2018
DOI: 10.3857/roj.2017.00591
|View full text |Cite
|
Sign up to set email alerts
|

Positional uncertainties of cervical and upper thoracic spine in stereotactic body radiotherapy with thermoplastic mask immobilization

Abstract: PurposeTo investigate positional uncertainty and its correlation with clinical parameters in spine stereotactic body radiotherapy (SBRT) using thermoplastic mask (TM) immobilization.Materials and MethodsA total of 21 patients who underwent spine SBRT for cervical or upper thoracic spinal lesions were retrospectively analyzed. All patients were treated with image guidance using cone beam computed tomography (CBCT) and 4 degrees-of-freedom (DoF) positional correction. Initial, pre-treatment, and post-treatment C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…In a previous study that evaluated setup errors in three directions, it was reported that the setup error was < 3 mm for head and neck radiotherapy treatment, which is consistent with the findings of this study for both patients using new and reused masks. In addition, this research is consistent with previous research, which investigated setup errors in different types of masks, and showed that the setup errors were < 2.4 mm [17][18][19][20].…”
Section: Issn 2672-9393supporting
confidence: 92%
“…In a previous study that evaluated setup errors in three directions, it was reported that the setup error was < 3 mm for head and neck radiotherapy treatment, which is consistent with the findings of this study for both patients using new and reused masks. In addition, this research is consistent with previous research, which investigated setup errors in different types of masks, and showed that the setup errors were < 2.4 mm [17][18][19][20].…”
Section: Issn 2672-9393supporting
confidence: 92%